2003
DOI: 10.1029/2003jc001922
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of flow variability in the Yucatan Channel

Abstract: [1] The structure and variability of the velocity and temperature fields in Yucatan Channel are analyzed using data from an eight-mooring array deployed from August 1999 to June 2000. The area-averaged kinetic energy and transport fluctuations spectra show that the extrema of these quantities do not coincide, and that flow variability is dominated by highly energetic processes with weak transport contributions. Transport fluctuations peak in the 20-40 and 5-10 day period bands, but show no clear correlation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
79
2
16

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(116 citation statements)
references
References 31 publications
19
79
2
16
Order By: Relevance
“…The strong variability are also seen in the cross-channel flows. As mentioned previously, Abascal et al [2003] reported mean cross-channel speeds of O(0. m s -) and standard deviation ≈ 0.5 m s -near the surface. The cross-channel currents are clearly time-dependent and not always negligible.…”
Section: Flowmentioning
confidence: 51%
See 2 more Smart Citations
“…The strong variability are also seen in the cross-channel flows. As mentioned previously, Abascal et al [2003] reported mean cross-channel speeds of O(0. m s -) and standard deviation ≈ 0.5 m s -near the surface. The cross-channel currents are clearly time-dependent and not always negligible.…”
Section: Flowmentioning
confidence: 51%
“…There is not (yet?) direct observational evidence of Caribbean eddies squeezing through the Yucatan Channel (though the Canek moorings across the channel suggest such a possibility; Abascal et al [2003]), but Murphy et al's numerical finding is interesting and potentially significant. Oey et al [2003] expanded upon Murphy et al's ideas, but instead of looking at the progression of individual eddies, they asked if forcing by winds (six-hourly ECMWF was used) and/or by Caribbean eddies (satellite SSH anomaly was used) would affect the statistics of ring-shedding, the periods in particular.…”
Section: Gulf Of Mexico and Caribbean Sea Connection Thementioning
confidence: 97%
See 1 more Smart Citation
“…Figure 1a shows the vertical section of the mean velocity across the Yucatan Channel from the 1/12° Atlantic system over the time period of September 2003 through August 2004. Observations of velocities from Abascal et al (2003) are shown in Figure 1b. The mean velocity/transport across 35°W between 5°S and 5°N from the model is shown in Figure 2a, while a corresponding plot of observations from Schott et al (2003) is shown in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
“…It is left to the user to model where the continuity (thickness tendency) equadefine the coordinate separation constraints that control tion is solved prognostically throughout the domain, regional transitions among the three coordinate choices with the Arbitrary Lagrangian-Eulerian (ALE) technique as described in the appendix. used to remap the vertical coordinate and maintain difAfter the model equations are solved, the hybrid ferent coordinate types within the domain (Adcroft and coordinate generator then relocates vertical interfaces to Hallberg, 2006). This differs from Eulerian Vertical restore isopycnic conditions in the ocean interior to the Direction (EVD) models with fixed z-and a-coordinates greatest extent possible while enforcing the minimum that use the continuity equation to diagnose vertical thickness requirements specified by (1) in the appendix.…”
Section: Introductionmentioning
confidence: 99%